HUBUNGAN PENGETAHUAN, DUKUNGAN KELUARGA, PERAN PETUGAS TERHADAP PEMANFAATAN POSYANDU LANSIA DI WILAYAH KERJA PUSKESMAS KONI TAHUN 2015 - Winda Triana (Jurnal Bahana Kesehatan Masyarakat (Bahana of Journal Public Health), 2016)
Life expectancy (UHH) is one of the indicators assessing the health status and quality of life, as well as thehuman development index (HDI) BPS data Jambi province UHH 2006 s / d in 2008 there was an increasefrom 68.5 years old, in 2007 to 68.6, and in 2009 reached 68.95 in 2010 reached 69.1. Data JambiProvince, the number of elderly inhabitants there are 261 680 registered in poksila is 125.80 (48.1%) withthe amount of 203 pieces poksila. Jambi city is the highest number of elderly (PHO Jambi, 2015) PHCKoni is a health center with a considerable number of elderly is 2,457 elderly, registered in Poksila is 836people, and visiting 405 elderly (Jambi City Health Office, 2015).This research is a quantitative research with cross sectional study design (Arikunto 2010) which aims todetermine the relationship of family support, and the role of the clerk of the behavior of health care visitselderly in Puskesmas Koni 2015. The population in this study were all enrolled in advanced age 2Puskesmas Posyandu elderly Koni 2015 with the number 836 and the sample 93 respondents drawn atrandom sampling study was conducted in February 2015. The analysis used univariate and bivariate. Thestatistical test used was chi Sguare (Arikunto, 2010).The result showed good behavior is less visits 50 (53.2%) and a good visit 43 (45.7%), Good knowledge of50 (53%) and lack of knowledge of both 43 (47%), less support either 49 (52.1%) and support both 44(46.8%), a role for either 56 (59.6%) less good role for 37 (39.4%), There is a correlation betweenknowledge, family support and the role of the clerk of the behavior of the elderly in Puskesmas Koni city ofJambi 2015.